Teachers’ Perceptions on Assessment for Learning in Geography: An Exploratory Approach - Retselisitsoe Lebona; Musa Adekunle Ayanwale (Studies in Learning and Teaching, 2024)
Assessment for Learning (AfL) plays a crucial role in the effective teaching and learning of Geography, offering educators a means to enhance student achievement. Through ongoing evaluations involving verbal and written exercises, AfL not only readies students for summative Assessment of Learning (AoL) but also supports them in grasping complex Geography concepts, features, and processes, as evidenced by examination performance. Over the last five years, as indicated by the Examinations Council of Lesotho, persistent challenges have emerged in this regard, potentially stemming from inadequacies in assessment strategies. This study delves into the perceptions of Geography teachers concerning Assessment for Learning. Employing a qualitative approach, the research utilizes non-participatory observations and in-depth interviews to collect data. The study is grounded in Gregory's Theory of Perception and Keeping Learning on Track Theory of Action, offering theoretical frameworks for analysis. The findings reveal that teachers face obstacles when implementing Assessment for Learning, including time constraints and issues related to classroom overcrowding. Notably, a significant insight is the lack of both Assessment knowledge and Pedagogical Content Knowledge among teachers. As a resolution, it is recommended that comprehensive assessment training be provided for both pre-service and in-service teachers, addressing these identified gaps.